THE INFLUENCE OF SELF-REGULATED LEARNING (SRL) SKILL ON STUDENTS’ ACHIEVEMENT IN ENGLISH SUBJECT AT THE ELEVENTH GRADE OF MA NW AL-AKHYAR LABUAPI LOBAR - Abi Firmansyah (Journal of English Education and Literature, 2026)
This research is aimed to determine the influence of Self-Regulated Learning (SRL) skills on students' achievement in English subject at the 11thgrade of MA NW Al-Akhyar Labuapi, Lobar. This research is ex-post facto research. The subjects in this research were all class XI students at MA NW Al-Akhyar Labuapi, totaling 50 students. Data collection techniques used psychological scales and documentation. The validity of the psychological scale was calculated by Pearson product moment correlation. Reliability was calculated using the Cronbach Alpha formula. Documentation was obtained from report cards for the 1stsemester of the 2022/2023 academic year. The data analysis technique was carried out using descriptive statistics. Hypothesis testing uses simple linear regression analysis.  The researcherfound that there was a significant influence of Self-Regulated Learning skills on students' achievement in English subject. This can be seen from the regression graph that the scattered points are close to the regression line and in the same direction as the regression line. The coefficient of determination (r2) value obtained was 0.348, indicating that the self-regulated learning skill factor influenced students' achievement in English subject by 34.8%, the remaining 65.2% was influenced by other factors.